Multiunit Accident Contributions to Quantitative Health Objectives: A Safety Goal Policy Analysis. (4th March 2017) - Hudson, Daniel W.; Modarres, Mohammad
Abstract: In 1986 the U.S. Nuclear Regulatory Commission (USNRC) implemented a safety goal policy in response to the 1979 Three Mile Island accident. This policy addresses the question, "How safe is safe enough?" by specifying quantitative health objectives (QHOs) for comparison with average individual early fatality and latent cancer fatality risk results computed from nuclear power plant (NPP) probabilistic risk assessments (PRAs). Comparisons of PRA results to the QHOs or other subsidiary numerical objectives are used to determine whether proposed regulatory actions should be rejected based on potential safety benefit relative to the level of residual risk to the public, before performing detailed cost-benefit analyses to determine whether they could be justified on their net value basis. Lessons learned from recent operational experience—including the 2011 Fukushima accident—indicate that concurrent accidents involving multiple units at a shared site can occur with non-negligible frequency. Yet, risk contributions from such scenarios are excluded by policy from safety goal evaluations for the nearly 60% of the U.S. NPP sites that include multiple units. The objectives of this paper are to (1) present an approach for estimating multiple unit risk metrics for comparison with the safety goal QHOs using accident scenarios from the State-of-the-Art Reactor Consequence Analyses (SOARCA) Project; and (2) using this approach, evaluate the effects of including risk contributions from concurrent multiunit accidents in safety goal evaluations. The approach is demonstrated using a two-unit case study involving two representative NPP sites that are each comprised of two co-located operating reactor units. This paper (1) summarizes results and insights obtained from the two-unit case study; (2) describes additional considerations for applying methods to sites comprised of two or more units, including other major radiological sources; and (3) identifies potential areas for further research.